Frequency of Helicobacter Pylori and Factors Affecting it in Patients Attending Check-up Policlinic of Cerrahpaşa Medical Faculty - TURFANER, Nurver; SÜT, Necdet; KAYPMAZ, Ayşe; SİPAHİOĞLU, Fikret (Cerrahpaşa Medical Journal, 2014)
Helicobacter pylori is the most common infection in the world and half of the world’s population is infected by this organism. The frequency in our country is 85% between ages 20-29 and 88 % between ages 60-69. In this study, H. Pylori was searched by Elisa Rapid Chromatographic test in 116 patients which were selected randomly from the patients referring to Cerrahpaşa Medical Faculty Family Medicine Check-up policlinic. Demographic and other factors which may affect its positivity were questioned. The frequency of H.Pylori was 50.8 % in the whole group. Men were affected 8 % more than women which was statistically insignificant. Factors affecting H. Pylori positivity were socioe-conomic level of the place of residence (61 %) and general gastro-intestinal symptoms (88 %). There were no relations between H.Pylori and eradication therapy, age, the number of persons in the house and stomach pain.